Solid state transformers topologies, controllers, and applications: State-of-the-art literature review - Abu-Siada, Ahmed; Budiri, J.; Abdou, A. (2018)
With the global trend to produce clean electrical energy, the penetration of renewable energy sources in existing electricity infrastructure is expected to increase significantly within the next few years. The solid state transformer (SST) is expected to play an essential role in future smart grid topologies. Unlike traditional magnetic transformer, SST is flexible enough to be of modular construction, enabling bi-directional power flow and can be employed for AC and DC grids. Moreover, SSTs can control the voltage level and modulate both active and reactive power at the point of common coupling without the need to external flexible AC transmission system device as per the current practice in conventional electricity grids. The rapid advancement in power semiconductors switching speed and power handling capacity will soon allow for the commercialisation of grid-rated SSTs. This paper is aimed at introducing a state-of-the-art review for SST proposed topologies, controllers, and applications. Additionally, strengths, weaknesses, opportunities, and threats (SWOT) analysis along with a brief review of market drivers for prospective commercialisation are elaborated.